Focal Vibration Alters Human Digital Sensory Nerve Action Potentials: A Pilot Study - Dong Qing Zhu; Fang Liu; Yu Zhu; Duan Lei; Xiang Jin; Lan Xu; Chao Jun Zheng; Robert Weber; Xiang Jun Chen (Neural Plasticity)
Introduction. We studied the impact of vibratory stimulation on the electrophysiological features of digital sensory nerve action potential (SNAP). Methods. The antidromic digit 3 SNAP was recorded in 19 healthy adults before, during, and after applying a vibration to either 3rd or 5th metacarpal phalangeal joint (MCPJ) at 60 Hz and amplitude of 2 mm. 100% supramaximal stimulus intensity was performed in 5 subjects (randomly selected from the 19 subjects) where the SNAP sizes were recorded. Results. The amplitude of digit 3 SNAP declined to 58.9±8.6% when a vibration was applied to MCPJ digit 3. These impacts did not change by increasing the electrical stimulus intensity. The SNAP regained its baseline value immediately after the cessation of vibration stimulation. The magnitude of size reduction of digit 3 SNAP was less when vibration was moved to from MCPJ of digit 3 to MCPJ of digit 5. Discussion. The marked drop of the SNAP size during vibratory stimulation reflects the decreased responsiveness of Aβ afferents to electrical stimulation, which deserve further investigation in the study of focal vibration in neurorehabilitation.